2019
DOI: 10.1039/c9sc00979e
|View full text |Cite
|
Sign up to set email alerts
|

Polyoxometalates as components of supramolecular assemblies

Abstract: The non-covalent interactions between polyoxometalates and inorganic- and organic-based moieties give rise to functional nanoassemblies with diverse potential in applied science.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
96
0
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 132 publications
(98 citation statements)
references
References 125 publications
0
96
0
2
Order By: Relevance
“…Thus, POMs exhibit outstanding physical, chemical, and biochemical properties that remain to be completely understood and applied. Due to these properties, POMs are studied in environmental, chemical, and industrial fields, particularly in the areas of catalysis, corrosion prevention, smart glasses, and macromolecular crystallography, as well as in biology, such as for cancer treatment, bacterial infection, and diabetes, among others [1][2][3][4][5][6]. Although the number of POM studies with anticancer effects is increasing, their mechanisms of action in each type of cancer cell are still far from being understood [3].…”
Section: Introductionmentioning
confidence: 99%
“…Thus, POMs exhibit outstanding physical, chemical, and biochemical properties that remain to be completely understood and applied. Due to these properties, POMs are studied in environmental, chemical, and industrial fields, particularly in the areas of catalysis, corrosion prevention, smart glasses, and macromolecular crystallography, as well as in biology, such as for cancer treatment, bacterial infection, and diabetes, among others [1][2][3][4][5][6]. Although the number of POM studies with anticancer effects is increasing, their mechanisms of action in each type of cancer cell are still far from being understood [3].…”
Section: Introductionmentioning
confidence: 99%
“…Their structural and chemical diversity can provide many attractivef unctionsa nd thusf acilitatearange of significant applications in catalysis, medicine, biology,e nergy,m aterials science and so forth. [3][4][5][6][7][8][9][10] More significantly,P OM clusters can be additionally functionalised with organic or biological molecules to further broaden the scope of their applicability. [11,12] Polymers are aw idely used class of materials because of their excellentp erformance and processability.T he development of advanced functionalp olymer materials is as traightforward strategy for meeting the needs of technological progress.…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, increasing their performance in SCs has become an important research direction. Numerous researchers have started developing composites based on POMs and high conductivity materials . In particular, the design and preparation of POMOFs had evolved into an effective strategy for achieving good dispersion of POMs at the molecular level and exposing more accessible active sites, thereby greatly increasing the specific surface area and pores of POMs.…”
Section: Introductionmentioning
confidence: 99%
“…Numerous researchers have startedd eveloping composites based on POMs and high conductivity materials. [29] In particular, the design and preparation of POMOFs had evolvedi nto an effective strategy for achieving good dispersion of POMs at the molecular level and exposing more accessible active sites, therebyg reatlyi ncreasingt he specific surfacea rea and pores of POMs. In 2017, Ma et al [30] reported the Keggin-based 3D coordinationp olymer,w hich was used as the electrode material, and showed that it had the capacitance of 206 Fg À1 and 81.7 %r etention after 1000 cycles.…”
Section: Introductionmentioning
confidence: 99%